The organisational structure of transnational narcotics trafficking groups in Southeast Asia: a case study of Vietnam’s border with Laos - Luong, Hai Thanh (Trends in organized crime, 2020)
The Golden Triangle - the area where the borders of Thailand, Laos, and Myanmar converge - is considered one of the most complicated narcotics-trafficking hotspots in the world. More research is needed, however, to understand the supply and demand resources as well as the overall structure of transnational narcotics trafficking (TransNT) in this area and neighboring regions. The present paper provides an in-depth examination of the organisational structure of TransNT in the borderland between Vietnam and Laos, using multiple qualitative approaches to identify four key aspects of trafficking groups in this area: namely, group size, the relative centrality of lead actors in the trafficking networks, the flexibility and adaptability of network operations, and the personal attributes of traffickers. Depending on the number of drug traffickers involved, TransNT in Vietnam can be separated into small, medium, and large-scale groups; however, drug markets in Vietnam are not controlled by monopolistic groups or ‘cartels’. Notably, cross-border networks tend to have a fluid structure characterised by a sophisticated modus operandi from the preparation stages to the later stages of trafficking activity, enabling the criminal networks to achieve their goals.